2016
DOI: 10.1021/jacs.6b04501
|View full text |Cite
|
Sign up to set email alerts
|

Linker Installation: Engineering Pore Environment with Precisely Placed Functionalities in Zirconium MOFs

Abstract: Precise placement of multiple functional groups in a highly ordered metal-organic framework (MOF) platform allows the tailoring of the pore environment, which is required for advanced applications. To realize this, we present a comprehensive study on the linker installation method, in which a stable MOF with coordinatively unsaturated Zr6 clusters was employed and linkers bearing different functional groups were postsynthetically installed. A Zr-MOF with inherent missing linker sites, namely, PCN-700, was init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
239
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 289 publications
(242 citation statements)
references
References 66 publications
(31 reference statements)
1
239
0
Order By: Relevance
“…Other ligands, including phosphates and sulfates, were also attached to the cluster of Zr‐MOFs by similar methods . A prominent example of dative PSM is the so‐called linker installation method in which a coordinatively unsaturated Zr‐MOF was constructed and linkers with different lengths were sequentially installed between each pair of clusters . Systematic variation of the pore volume and decoration of pore environment were realized by sequential installation of multiple linkers with different lengths or functional groups, which resulted in synergistic effects in gas uptake.…”
Section: Design and Synthesismentioning
confidence: 99%
“…Other ligands, including phosphates and sulfates, were also attached to the cluster of Zr‐MOFs by similar methods . A prominent example of dative PSM is the so‐called linker installation method in which a coordinatively unsaturated Zr‐MOF was constructed and linkers with different lengths were sequentially installed between each pair of clusters . Systematic variation of the pore volume and decoration of pore environment were realized by sequential installation of multiple linkers with different lengths or functional groups, which resulted in synergistic effects in gas uptake.…”
Section: Design and Synthesismentioning
confidence: 99%
“…Post-synthetic methods such as covalent and coordinative modification, deprotection, solventassisted ligand exchange or insertion provide further possibilities to precisely engineer the framework according to the desired applications. [4][5][6] These applications range from catalysis, 7 gas separation and storage, 8 to drug delivery, electrochemistry 9 and chemical sensing, 10 among many others, where post-synthetic treatment can lead to a significant improvement of the material performance. [11][12][13] When it comes to sensing applications, the stimuli-responsive material is required to exhibit a property change upon analyte exposure that can be measured as a sensing signal.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, a linker with a hemicyanine moiety was synthesized, denoted as L2Hcy. Previous studies have demonstrated that two linkers with lengths similar to L1 and L2Hcy can be simultaneously installed into PCN‐700 by insertion into the unsaturated Zr sites . In this work, however, it was discovered that the two linkers could not be installed simultaneously.…”
Section: Figurementioning
confidence: 76%
“…Herein, we report a turn‐on fluorescence sensor generated through the combination of an anthracene‐based fluorophore and a hemicyanine‐based CN − ‐responsive moiety in a multicomponent MOF (Figure ). A stable MOF with coordinatively unsaturated Zr sites, namely PCN‐700, was selected as a matrix in order to generate a multifunctional MOF . The coordinatively unsaturated sites within PCN‐700 form two types of pockets, each accommodating only one of two organic linkers, each with different lengths.…”
Section: Figurementioning
confidence: 99%